Islam and Legislation of Human Rights: A Study into its Orientation, Evolution and Progression - Khan, Muhammad Mumtaz Ali; Hussain, Mazher; Khan, Muhammad Danyal (Annals of Human and Social Sciences, 2023)
Human Rights are universal in nature and scope and so is the Islam. After 9/11, the issue of security and sanctity of these rights was raised, especially in the Western scholarship. Some pointed out that there was a wide gap between East and West; hence the scholars like Samuel P. Huntington termed it a “Clash of Civilization” that will ultimately lead towards the supremacy of the Western Culture. Some called it the “End of History. Especially; Islam was considered as the main focus and target and was called a barbaric religion incompatible with the modern-day needs. The research in hand is an effort to discuss the history and evolution of the Human Rights through ages and it has been proved with examples that the modern-day Human Rights legislation or enactment and a number of Internationally developed and acclaimed documents contain almost all the ingredients which are found in the documents of Hudaibiya and Medina treaties, and the Last Sermon of the Holy Prophet (PBUH). Comparisons have also been made where it had been deemed necessary. In the end the summative history of Human Rights development and the postulates of aforementioned sermon have also been discussed to show the impact.